2022
DOI: 10.1007/s11104-022-05492-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of water repellency by leaves of contrasting Australian native species: effects of composition and heating

Abstract: Aims This study identifies the contribution of leaf matter from individual plant species on water repellency with a focus on the composition of organic compounds and the role of heat in releasing these compounds to soil. Methods Leaf powder from four plant species (Banksia menziesii, Eucalyptus marginata, Allocasuarina fraseriana, Xanthorrhoea preissii) was mixed with acid-washed sand (AWS) under a range of temperatures and WR measured. Plant chemical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…These results are comparable with Novák et al (2009), who reported a decline in SWR with increasing temperature in Meadow and Pine Forest soils. Dao et al (2022) and Doerr et al (2005) also reported an increase in SWR with increasing temperature up to about 150 °C, following a decline in SWR with heating beyond 150 °C.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…These results are comparable with Novák et al (2009), who reported a decline in SWR with increasing temperature in Meadow and Pine Forest soils. Dao et al (2022) and Doerr et al (2005) also reported an increase in SWR with increasing temperature up to about 150 °C, following a decline in SWR with heating beyond 150 °C.…”
Section: Resultsmentioning
confidence: 83%
“…In general, the organic matter contents of aggregates decreased with increasing depth, TH, and ED. Soil organic matter is crucial for the occurrence of SWR under both burned and unburned conditions (Atanassova and Doerr, 2010;Dao et al, 2022). In our study, we evaluated the relationship between soil organic matter content and SWR by examining contact angles (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations